Early versus late leaf removal strategies for Pinot Noir (Vitis vinifera L.): effect on colour‐related phenolics in young wines following alcoholic fermentation. (14th June 2013) - Sternad Lemut, Melita; Trost, Kajetan; Sivilotti, Paolo; Arapitsas, Panagiotis; Vrhovsek, Urska
Abstract: Background: The widely adopted viticultural practice of late (véraison) leaf removal is now losing many of its advantages as a result of today's warmer vineyard conditions. With the aim of seeking a good alternative, the influence of earlier leaf removals (at pre‐flowering and berry‐set) on colour‐related phenolics in young Pinot Noir wines was investigated in the years 2009 and 2010 . Results: Total flavonols in 2009 wines were 71 and 52% higher in case of véraison and berry‐set treatments respectively as compared with untreated controls, while in 2010 the average content of flavonols was highest with pre‐flowering leaf removal (75% higher than controls). The anthocyanin content in 2009 wines was 18 and 11% higher in case of véraison and berry‐set treatments respectively and was favoured by early leaf removals in 2010 (50 and 43% higher in case of berry‐set and pre‐flowering treatments respectively) as compared with controls. Changes in hydroxycinnamic acid profiles were shown to be greatest in 2010 wines resulting from early leaf removal treatments. Promoted formation of vitisin A‐like pigments in 2010 leaf removal treatments was observed during fermentation . Conclusions: The phenolic profiles of grapes/wines were affected by leaf removal timing, although differently in two (extremely different) seasons. Earlier leaf removal strategies showed some promising results, with good proportions mainly of flavonols and anthocyanins, retained also in young wines. Vitisins A in wines were positively affected by all leaf removals. © 2013 Society of Chemical Industry